2005
DOI: 10.1196/annals.1327.020
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Balance in Ruminants: Adaptation to External and Internal Challenges

Abstract: Ruminants are widespread in hot, arid regions. This demands adaptation to large circadian temperature fluctuations and recurrent periods of food and water shortage. Pregnancy and lactation add to the demands on the adaptive mechanisms due to the greater need for food, water, and electrolytes. The blood volume increases to meet the requirements of the fetoplacental unit and the mammary glands. Unlike urine, the milk cannot be concentrated by antidiuretic hormone (vasopressin). During water deprivation, lactatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
1
15
0
8
Order By: Relevance
“…However, it has been shown that hematocrit is not a reliable indicator of dehydration because it is highly variable (Parker et al, 2004;Scharf et al, 2008b). One rapid response to dehydration is a significant reduction in feed intake (Bianca et al, 1965;Olsson, 2005;Scharf et al, 2008b). Even though animals in the current study were limit-fed, dehydration should have resulted in some reduction in feed consumption.…”
Section: Discussionmentioning
confidence: 68%
“…However, it has been shown that hematocrit is not a reliable indicator of dehydration because it is highly variable (Parker et al, 2004;Scharf et al, 2008b). One rapid response to dehydration is a significant reduction in feed intake (Bianca et al, 1965;Olsson, 2005;Scharf et al, 2008b). Even though animals in the current study were limit-fed, dehydration should have resulted in some reduction in feed consumption.…”
Section: Discussionmentioning
confidence: 68%
“…This explains why dehydrated goats and sheep decrease their urine volume while the osmolality and vasopressin levels augment. Olsson (2005) [113] noted that thermoregulation and fluid balance, as regulated by thirst control, vasopressin secretion, sodium balance and other osmotic and cardiovascular signals, seem to be centrally regulated at the hypothalamic level, particularly the preoptic and anterior hypothalamic neurons. Silanikove (1994) [15] presents a detailed account of the dynamics of major electrolytes under dehydration in connection with water conservation and homeostatic mechanisms in ruminants.…”
Section: Electrolytes and Osmolalitymentioning
confidence: 99%
“…Dehydration reduces productivity (e.g. in plants; Farooq et al, 2009), alters blood chemistry (Hamadeh et al, 2006) and causes other alterations in physiology or behavior (Olsson, 2005;Dupoué et al, 2014). Furthermore, as both survival and reproduction rely on the availability of sufficient water resources, water imbalance can reduce animal fitness.…”
Section: Introductionmentioning
confidence: 99%